The Roles of Fractionated Potentials in Non-Macroreentrant Atrial Tachycardias Following Atrial Fibrillation Ablation: Recognition Beyond Three-Dimensional Mapping - Wang, Yu-Chuan; Shi, Li-Bin; Chu, Song-Yun; Solheim, Eivind; Schuster, Peter; Chen, Jian (Frontiers in Cardiovascular Medicine, 2022)
Introduction Non-macroreentrant atrial tachycardia (nAT) following atrial fibrillation (AF) ablation is being increasingly reported. Many issues remain to be elucidated. We aimed to characterize the fractionated potentials (FPs) in nAT and introduce a new method of cross-mapping for clarifying their roles. Methods and Results Forty-four nATs in 37 patients were enrolled and classified into focal AT (FAT, 12), microreentrant AT (MAT, 14), and small-loop-reentrant AT (SAT, 18) groups, according to activation pattern. FP was found on all targets except in nine FATs. The ratio of FP duration to AT cycle length (TCL) was different among groups (28 ± 7% in FAT, 53 ± 11% in MAT, and 42 ± 14% in SAT, p < 0.05), and ablation duration were longer in SATs (313 ± 298 vs. 111 ± 125 s, p < 0.05). The ratio of mappable cycle length to TCL was lower in the FAT group (63 ± 22% vs. 90 ± 9% and 89 ± 8%, p < 0.05). When cross-mapping was employed, trans-potential time differences in both longitudinal and transverse direction were longer around the culprit FP for MAT (p < 0.01). After Receiver Operating Characteristic curve analysis, it is best to adopt the sum of time difference ratios in both directions ≥60% as a cut-off value for discrimination of the FPs responsible for MAT with a sensitivity of 92% and specificity of 87%. Conclusions FP could be found on target in most nATs following a previous AF ablation. The ratio of FP duration to TCL may help for differentiation. A simple method of cross-mapping could be employed to clarify the roles of FPs.